2021
DOI: 10.3389/fmicb.2021.729900
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activity of Contezolid Against Methicillin-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococcus, and Strains With Linezolid Resistance Genes From China

Abstract: Contezolid is a novel oxazolidinone, which exhibits potent activity against gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and penicillin-resistant Streptococcus pneumoniae (PRSP). In this study, the in vitro activity of contezolid was compared with linezolid (LZD), tigecycline (TGC), teicoplanin (TEC), vancomycin (VA), daptomycin (DAP), and florfenicol (FFC) against MRSA and VRE strains isolated from China. Contezolid revealed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
0
8
0
Order By: Relevance
“… 8 According to a recent study, contezolid exhibited considerable activity in vitro against VRE isolates. 27 In addition to cSSTI, contezolid has also been found to be effective in lung infections, such as pulmonary tuberculosis. 28 , 29 Based on our knowledge, this is the first published report of a patient with VREfm pneumonia who was treated successfully with contezolid.…”
Section: Discussionmentioning
confidence: 99%
“… 8 According to a recent study, contezolid exhibited considerable activity in vitro against VRE isolates. 27 In addition to cSSTI, contezolid has also been found to be effective in lung infections, such as pulmonary tuberculosis. 28 , 29 Based on our knowledge, this is the first published report of a patient with VREfm pneumonia who was treated successfully with contezolid.…”
Section: Discussionmentioning
confidence: 99%
“…Oxazolidinones, including linezolid, contezolid, and tedizolid, are applied as the first-line drug for the antimicrobial treatment of gram-positive bacterial infections. Multiple reports have shown the excellent antibacterial activity of radezolid against the planktonic cells of gram-positive bacteria ( Moellering, 2014 ; Zheng J. et al, 2020 ; Wang et al, 2021 ). A previous study shows that radezolid still has potent antibacterial activity against E. faecalis linezolid non-susceptible strains, with the MIC of radezolid being 2–8 times lower than that of linezolid ( Zheng J. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, contezolid had good antibacterial activity against aerobic GPB, especially against the drug-resistant strains of such aerobic Gram-positive cocci as MRSA, penicillin-resistant S. pneumoniae (PRSP), and VRE. Of note, a previous study indicated that contezolid had limited activity against strains carrying linezolid-resistance genes, such as Staphylococcus capitis with the cfr gene and E. faecalis with the optrA gene, and vanA - and vanM- type VRE strains ( Wang et al, 2021a ). Moreover, compared with linezolid, contezolid was active against most non-tuberculous Mycobacterium reference strains, with the exception of Mycobacterium avium and Mycobacterium intracellulare , and pre-exposure to contezolid did not induce drug resistance ( Wilcox, 2005 ; Guo et al, 2021 ).…”
Section: Antibacterial Efficacymentioning
confidence: 99%